2018
DOI: 10.5252/zoosystema2018v40a6
|View full text |Cite
|
Sign up to set email alerts
|

Article 23.9 of theCodecannot be used to reject the nomenHyla quoyiBory de Saint-Vincent, 1828 as anomen oblitum

Abstract: Article 23.9 of the Code, introduced in its last 1999 version, allows the validation, in some cases, of a well known junior synonym or homonym as opposed to a senior synonym or homonym that had been ignored in the literature after 1899. In such cases, the junior nomen qualifies as a nomen protectum and the senior one as a nomen oblitum, a formula redefined in a new sense in this edition. The implementation of this Article requires one to follow strictly several conditions: the invalidation can concern only sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Caramaschi and Niemeyer (2010) then considered Hyla quoyi an unavailable name (erroneously, and based on Frost's (2010) assertion), and stated that "Hypsiboas prasinus (Burmeister, 1856) is a nomen protectum (ICZN 1999) relative to Hyla quoyi Bory de Saint-Vincent, 1828, a nomen oblitum.". We agree with Ohler and Dubois (2018) that this nomenclatural act made by Caramaschi and Niemeyer (2010) is not valid because Hyla quoyi was then (as it is now) an available name, and, mainly, because it was not justified with evidence that the conditions stated in Article 23.9.1 were met (Article 23.9.2). But, the fact is that Caramaschi and Niemeyer's (2010) conclusion is inherently right, since Hyla prasina (=Hypsiboas prasinus) actually met at that time the conditions to be considered a nomen protectum under Article 23.9.1, that is, a reversal of precedence over Hyla quoyi (see below).…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Caramaschi and Niemeyer (2010) then considered Hyla quoyi an unavailable name (erroneously, and based on Frost's (2010) assertion), and stated that "Hypsiboas prasinus (Burmeister, 1856) is a nomen protectum (ICZN 1999) relative to Hyla quoyi Bory de Saint-Vincent, 1828, a nomen oblitum.". We agree with Ohler and Dubois (2018) that this nomenclatural act made by Caramaschi and Niemeyer (2010) is not valid because Hyla quoyi was then (as it is now) an available name, and, mainly, because it was not justified with evidence that the conditions stated in Article 23.9.1 were met (Article 23.9.2). But, the fact is that Caramaschi and Niemeyer's (2010) conclusion is inherently right, since Hyla prasina (=Hypsiboas prasinus) actually met at that time the conditions to be considered a nomen protectum under Article 23.9.1, that is, a reversal of precedence over Hyla quoyi (see below).…”
mentioning
confidence: 70%
“…It is clear from the previous paragraph that Ohler and Dubois' (2018) intention was to determine if Hyla prasina met the conditions of Article 23.9 for a reversal of precedence and they concluded that it did not. But, contrary to Ohler and Dubois (2018), we are aware of a well-established and widespread use of the name Hyla prasina (=Hypsiboas prasinus) in the zoological literature, so we performed a manual search among many published papers, and we found evidence that Hyla prasina Burmeister, 1856 actually complies with the requirements of Article 23.9.1 of the Code for a reversal of precedence over Hyla quoyi Bory de Saint-Vincent, 1828. Since Ohler and Dubois' (2018) nomenclatural act is based on a false premise ("that the conditions of implementation of Article 23.9 are not complied with"), and their conclusion is wrong (that then "the regular Rules of the Code must be applied"), we do not accept as valid the usage of Boana quoyi (=Hyla quoyi) in Ohler and Dubois' (2018) work for the purpose of application of Article 23.9.1.1, and consequently, any eventual posterior usage of this name following Ohler and Dubois (2018).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…To the best of our knowledge, none (except L. lemniscatus ) of the Liolaemus nomina coined by Gravenhorst (1838) were used as valid names after 1899; however, this does not make them ‘forgotten names’, because only senior, and not junior, synonyms can be nomina oblita (Ohler & Dubois, 2018).…”
Section: Discussionmentioning
confidence: 99%